2005
DOI: 10.1074/jbc.m505733200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation-independent Effect of Histone Deacetylase Inhibitors on Akt through the Reshuffling of Protein Phosphatase 1 Complexes

Abstract: Despite advances in understanding the role of histone deacetylases (HDACs) in tumorigenesis, the mechanism by which HDAC inhibitors mediate antineoplastic effects remains elusive. Modifications of the histone code alone are not sufficient to account for the antitumor effect of HDAC inhibitors. The present study demonstrates a novel histone acetylation-independent mechanism by which HDAC inhibitors cause Akt dephosphorylation in U87MG glioblastoma and PC-3 prostate cancer cells by disrupting HDACprotein phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
198
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(217 citation statements)
references
References 41 publications
16
198
3
Order By: Relevance
“…This concentration of VN/66-1 is biologically relevant, because it is well below the maximum plasma concentration (26.9 mM), which was achieved in mice following a single subcutaneous administration of 10 mg kg À1 of VN/66-1 (Patel et al, 2007a). It should also be noted that these concentrations of MS-275 have been used previously for a similar study using PC-3 cells (Chen et al, 2005). Furthermore, it has been reported that MS-275 has an IC 50 value of 4.8 mM in inhibiting HDAC activity in nuclear extracts (Miller et al, 2003).…”
Section: Resultsmentioning
confidence: 91%
“…This concentration of VN/66-1 is biologically relevant, because it is well below the maximum plasma concentration (26.9 mM), which was achieved in mice following a single subcutaneous administration of 10 mg kg À1 of VN/66-1 (Patel et al, 2007a). It should also be noted that these concentrations of MS-275 have been used previously for a similar study using PC-3 cells (Chen et al, 2005). Furthermore, it has been reported that MS-275 has an IC 50 value of 4.8 mM in inhibiting HDAC activity in nuclear extracts (Miller et al, 2003).…”
Section: Resultsmentioning
confidence: 91%
“…33 In addition, other investigators found that SAHA as well as tricostatin A inhibited Akt activity in prostate cancer cells. 34 These observations suggested that Akt signal pathway may be a common target of HDACI.…”
Section: Discussionmentioning
confidence: 99%
“…SAHA is an HDAC inhibitor, which has been shown to be active against breast cancer cells, through induction of cell cycle arrest, apoptosis and differentiation (29,42). Recent data suggest that, independent of its activity as an HDAC inhibitor, SAHA can also activate caspases and inhibit AKT phosphorylation (42,43). Thus, SAHA may share common mechanisms of action with HNK.…”
Section: Discussionmentioning
confidence: 99%